Bridging Cultures Through Language: Developing English-Speaking Materials for Multicultural Education Contexts: - Hidayah, Hidayah; Sahraini, Sahraini; Jufriadi, Jufriadi (Elsya : Journal of English Language Studies, 2024)
Indonesia's rich multicultural diversity often presents challenges such as prejudice and violence, emphasizing the need for effective multicultural education to foster unity among teenagers. This study uniquely addresses this gap by developing multicultural-based English teaching materials aimed at enhancing students' vocabulary, cultural understanding, and speaking skills. Conducted at SMAN 9 Luwu with 30 eleventh-grade students and experienced teachers, the research employed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The analysis phase highlighted a significant need for multicultural education materials, specifically to improve speaking skills. During the design and development phases, the materials were carefully crafted to incorporate multicultural themes and improve language proficiency. In the implementation phase, the materials were tested in a classroom setting, and data were collected through observations, questionnaires, and assessments. The results demonstrated substantial improvements in students' speaking abilities, with expert evaluations confirming the effectiveness and cultural relevance of the materials. The evaluation phase provided both formative and summative assessments, revealing that students not only enhanced their language skills but also developed a greater appreciation for cultural diversity. This research highlights the importance of integrating multicultural perspectives into educational resources, enhancing language proficiency and cultural competence. The findings support broader adoption of multicultural education strategies to promote equity and excellence.